PERLINDUNGAN TERHADAP PEMEGANG RUANG HAK ATAS TANAH ATAS PEMANFAATAN RUANG BAWAH TANAH - Adi, Dwi Laksono; Nuryanti, Aktris; Asikin, Uti (Tanjungpura Acta Borneo Jurnal, 2022)
Abstract  Utilization of underground space is the fulfillment of public interest needs such as the construction of underground transportation lines such as MRT, shops, parking areas and others. The use of underground space has an influence on the regulation of land rights institutions, if there is no deep thought that will result in the emergence of legal and social problems that become obstacles to development. Utilization of the basement can not be separated from a problem and a constraint. In this case, there are two ownerships of the basement, besides that the party who is disadvantaged is the holder of the land right because there is a use of the underground space that passes through the owner of the land right. protection of land rights holders. The research method used by the author in writing is a normative research method by analyzing secondary data in the form of primary legal materials and secondary legal materials. The data were collected using library research techniques and analyzed normatively. The type of approach used is the case and law approach. The results of the study revealed that there was no regulation regarding dungeons. According to PP 18 of 2021, basements as implementing regulations of Number 11 of 2020 concerning Job Creation, basements are land that is structurally or functionally separate from the holder of Land Rights. In other cases, there are two ownerships of the basement so that there is legal uncertainty about the basement, the UUPA states that the bowels of the earth are land rights that we can use. In addition, compensation is an obstacle to the use of the basement, there are parties who are disadvantaged in the use of the basement in terms of law and architecture. Therefore, it is necessary to have a law that regulates basements in order to get clarity on the use of basements. It is necessary to think about the underground space because land is an aspect of every human right.Keywords: compensation; underground space; regulations    Abstrak  Pemanfaatan ruang bawah tanah merupakan pemenuhan kebutuhan kepentingan umum seperti pembangunan jalur transportasi bawah tanah seperti MRT, pertokoan, area parkir dan lain-lain. Penggunaan ruang di bawah tanah membawa pengaruh terhadap pengaturan lembaga hak atas tanah, apabila tidak diadakan pemikiran mendalam yang akan berakibat timbulnya masalah hukum maupun sosial yang menjadi kendala pembangunan. Pemanfaatan ruang bawah tanah tidak terlepas dari suatu masalah dan kendala. Dalam hal ini terdapat dua kepemilikan terhadap ruang bawah tanah selain itu pihak yang dirugikan yaitu pemegang hak atas tanah dikarnakan terdapat suatu pemanfaatan ruang bawah tanah yang melintas pemilik hak atas tanah selain itu masalah lain muncul dalam pemanfaatan tanah adalah perundang-undangan dibidang pertanahan yang tidak memberikan perlindungan pemegang hak atas tanah. Metode penelitian yang dilakukan penulis dalam melakukan penulisan adalah metode penelitian normatif dengan menganalisa data sekunder berupa bahan hukum primer dan bahan hukum sekunder. data tersebut dikumpulkan menggunakan Teknik studi kepustakaan dan dianalisis secara normatif. Jenis Pendekatan yang digunakan adalah jenis pendekatan kasus dan undang "“ undang. Hasil penelitian mengungkapkan belum terdapat suatu peraturan tentang ruang bawah tanah. menurut PP 18 tahun 2021 ruang bawah tanah sebagai peraturan pelaksana dari UU Nomor 11 Tahun 2020 tentang Cipta Kerja ruang bawah tanah merupakan Tanah yang secara struktur atau fungsi terpisah dari pemegang Hak Atas Tanah. Dalam hal lain terdapat dua kepemilikan terhadap ruang bawah tanah sehingga terdapat ketidakpastian hukum tentang ruang bawah tanah, UUPA menyebutkan perut bumi merupakan hak milik tanah yang dapat kita gunakan. Selain itu ganti rugi menjadi kendala dari pemanfaatan ruang bawah tanah, terdapat pihak yang dirugikan dalam pemanfaatan ruang bawah tanah dari segi hukum dan arsitektur. Maka dari itu diperlukan undang "“ undang yang mengatur tentang ruang bawah tanah agar mendapat kejelasan terhadap pemfaatan ruang bawah tanah. Perlu dilakukan pemikiran terkait ruang bawah tanah dikarnakan tanah adalah aspek hak setiap manusia.Kata Kunci: ruang bawah tanah; kompensasi; regulasi